2022
DOI: 10.3389/fnbeh.2021.799271
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake Rhythm and Oscillatory Pattern Analysis in a Multiple Hit Schizophrenia Rat Model (Wisket)

Abstract: Electroencephalography studies in schizophrenia reported impairments in circadian rhythm and oscillatory activity, which may reflect the deficits in cognitive and sensory processing. The current study evaluated the circadian rhythm and the state-dependent oscillatory pattern in control Wistar and a multiple hit schizophrenia rat model (Wisket) using custom-made software for identification of the artifacts and the classification of sleep-wake stages and the active and quiet awake substages. The Wisket animals h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 100 publications
(188 reference statements)
0
1
0
Order By: Relevance
“…The Wisket animals showed a wide range of behavioral disturbances including impaired pain sensitivity, sensory gating, and cognition [ 16 , 17 , 18 , 19 ]. Alterations in opioid, cannabinoid, oxytocin, and dopamine receptor (D 2 R and D 1 R) signaling and/or expression together with electroencephalography changes were also detected [ 14 , 18 , 20 , 21 , 22 , 23 ]. Furthermore, a histological study revealed significant decreases in the frontal cortical thickness and the hippocampal area, moderate increases in the lateral ventricles, and cell disarray of the CA3 subfield of the hippocampus of the Wisket animals [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Wisket animals showed a wide range of behavioral disturbances including impaired pain sensitivity, sensory gating, and cognition [ 16 , 17 , 18 , 19 ]. Alterations in opioid, cannabinoid, oxytocin, and dopamine receptor (D 2 R and D 1 R) signaling and/or expression together with electroencephalography changes were also detected [ 14 , 18 , 20 , 21 , 22 , 23 ]. Furthermore, a histological study revealed significant decreases in the frontal cortical thickness and the hippocampal area, moderate increases in the lateral ventricles, and cell disarray of the CA3 subfield of the hippocampus of the Wisket animals [ 24 ].…”
Section: Introductionmentioning
confidence: 99%